A Mini-Review on Overcoming a Calorie-Centric World of Monolithic Annual Crops - Snapp, Sieglinde (Frontiers in Sustainable Food Systems, 2020)
There is widespread recognition that a narrow crop base has inherent vulnerabilities. Crop diversification is one strategy that can help enhance human health, environmental sustainability and resilience of farming communities – yet lock-in mechanisms have mediated against such diversification. This mini-review considers inadvertent negative impacts on crop diversity of policies that favor a few, highly annual crops. Priorities of agricultural research and government institutions such as Public Distribution Systems promote production of a few determinant cereal species, and do not consider the ecosystem service functions associated with diverse growth types, e.g., long duration, indeterminant and perennial crops. Genetic improvement of fields crops has prioritized short maturity cycles, calorie production, and inadvertently, this may lead to high consumption of water and nutrients. Such crops are highly productive; however, they ‘lock-in’ dependence on fossil fuels and chemical pest regulation. Further, early duration crops have modest root systems, and are short-statured. This limits generation of co-products, such as fodder, fuel wood, leafy vegetables and soil amelioration. Research gaps and next steps are proposed to address this challenge, including: 1) investigation of adoption barriers and opportunities in order to foster diverse crop growth types and ‘bright spots’ of agroecosystem diversity, 2) changing metrics for assessing system performance, to consider nutrient-enrichment, multipurpose properties and ecosystem services in agricultural policy, and 3) investment in developing perennial and multipurpose grain crops, and plant-facilitated nutrient accessing mechanisms. Enhanced resilience in agriculture requires greater attention to promotion of crop diversity, including functional diversity and socio-economic innovations.